In the footsteps of Ramazzini: Modern occupational medicine and the role of occupational epidemiology - Francesco CHIRICO (GIornale Italiano di Psicologia e Medicina del Lavoro, 2024)
This editorial revisits the foundational contributions of Bernardino Ramazzini to occupational medicine and their relevance in today’s context. Ramazzini, born in 1633 in Italy, pioneered occupational neurotoxicology in his 1700 treatise, “De Morbis Artificum Diatriba,” linking heavy metal exposure to neurological disorders in workers. His extensive work spanned various fields, including studies on artesian aquifers, atmospheric impacts on epidemics, and early advocacy for quinine in malaria treatment. A significant part of his legacy was at the University of Modena, where he methodically documented health issues across professions, emphasizing a healthy workforce for societal productivity. The editorial highlights how modern occupational physicians continue to draw from Ramazzini’s principles, focusing on detailed observation and systematic recording of occupational diseases. The cornerstone of current practice is epidemiological analysis, which aims to identify relationships between workplace exposures and health outcomes. This approach is exemplified by establishing occupational cancer registries and correlating specific cancers with job exposures. Moreover, the role of technology and collaboration in enhancing data collection and analysis is discussed, alongside the need for continuous learning and advocacy in occupational medicine. Conclusively, Ramazzini’s legacy endures in today’s data-driven healthcare environment, guiding occupational health professionals in protecting workers and evaluating preventive measures’ effectiveness.